Identifikasi Faktor-Faktor Kesuksesan Start Up Digital di Kota Bandung - Rudi Hardiansyah; Dodie Tricahyono (Jurnal Ekonomi, 2019)
According research from Center for Human Genetic Research (CHGR), amount of digital start up of Indonesia in 2020 reach 13.000 start up. Nowadays Indonesia, with 1.939 company of digital start up, touches 6th position country as the greatest amount of start up in the world. Nevertheless, data showed that the number of failed start up still high. According research from Shikar Gosh, the number of failed digital start up reach 95%. In othe side, data from one of digital start up incubator in Bandung, the number of failed digital start up reach 62,2%.Some start up can learn from oldest success start up as reference. This research be intended to seeing factors whether successfull digital start up, especially in Bandung City. This research is qualitative with 6 respondend contains the owner of start up, manager of incubator, and coach of developer digital start up in Bandung. The method used is literature manufacturing, observation to incubator, also deep interview to respondend. By this research, there are 11 factors deciding whether a digital start up are success, those are: Synergy, product, process, managerial innovation, communication, culture, experience, information technology, innovation skills, functional skills, and implementation skills. The research showed 10 of 11 variable thorough are influence factors in digital start up successful information technology doesnt influence enough. Depend on result, this research can suggest some point to start up enterpreneur, incubator organization, also for the next research. To be intended the founder of digital start up could be better, especially in incubator organization so the number of success digital start up would rise up.